Oxford Scholarship Online 2018
DOI: 10.1093/oso/9780190465285.003.0008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ancestry Tests and Race

Abstract: This chapter probes genetic ancestry tests, which are being used increasingly by individuals for a number of reasons. Many are seeking ways to fill in gaps in their family tree; some are hoping to assert membership in certain groups or tribes; and others are simply curious. Nearly 500 test-takers filled out an online survey with questions attempting to form a basis of understanding about the types of people who take these tests, why they take them, and the impact the results have on their identity. There are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Because we used Bayesian analyses, replicated our effects across two different experimental paradigms, used a variety of methods to isolate the influence of receiving one's DNA ancestry results from confounding factors (e.g., the act of taking a test, information about their genetic relatives, the opinions of others) and used two different measures of genetic knowledge, we provide new evidence that the degree of knowledge about genetics is unlikely to influence responses to DNA ancestry results, at least in the present context and population. Our findings also appear consistent with additional research using nonexperimental methods (see Hochschild & Sen, 2015;Roth & Lyon, 2018;Scully et al, 2016). More specifically, a survey of people's retrospective responses to their own DNA ancestry results suggests that only a small percentage of people may fully embrace their new identities or engage in meaningful new intergroup interactions (Roth & Lyon, 2018).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Because we used Bayesian analyses, replicated our effects across two different experimental paradigms, used a variety of methods to isolate the influence of receiving one's DNA ancestry results from confounding factors (e.g., the act of taking a test, information about their genetic relatives, the opinions of others) and used two different measures of genetic knowledge, we provide new evidence that the degree of knowledge about genetics is unlikely to influence responses to DNA ancestry results, at least in the present context and population. Our findings also appear consistent with additional research using nonexperimental methods (see Hochschild & Sen, 2015;Roth & Lyon, 2018;Scully et al, 2016). More specifically, a survey of people's retrospective responses to their own DNA ancestry results suggests that only a small percentage of people may fully embrace their new identities or engage in meaningful new intergroup interactions (Roth & Lyon, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Our findings also appear consistent with additional research using nonexperimental methods (see Hochschild & Sen, 2015;Roth & Lyon, 2018;Scully et al, 2016). More specifically, a survey of people's retrospective responses to their own DNA ancestry results suggests that only a small percentage of people may fully embrace their new identities or engage in meaningful new intergroup interactions (Roth & Lyon, 2018). Furthermore, studies using qualitative interviews (Scully et al, 2016) and responses to vignettes (Hochschild & Sen, 2015) also suggest that how people incorporate new ancestry information into their lives may be much more subtle than previously assumed.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For example, previous work shows that people (e.g., African Americans) use biogeographic ancestry information to (re)construct their own racial identities and the extent to which they affiliate with racial/ethnic groups (Lawton & Foeman, 2017; Morning, 2017; Nelson, 2008; Nelson, 2016). Roth and Lyon (2018) found that 73.9% of about 600 individuals who took genetic ancestry tests reported that the biogeographic ancestry information affected how they racially identified. Even more telling, some people reported that they changed their racially/ethnically identification and/or sought new affiliations with other racial/ethnic groups based on their biogeographic ancestry results (as cited in Heine et al, 2017; Morning, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[3] Most people seek out consumer genetic testing to trace their ancestry, both to identify relatives as well as to discover or confirm one's ethnic heritage. [50] 23andMe was the first service to offer both ancestry testing and information about inherited traits and diseases. In addition to providing direct individual benefits, some services also aim for a higher calling: asking users to contribute their DNA to genomic research projects.…”
Section: Introductionmentioning
confidence: 99%